Correlation of Reflux Symptom Index and Reflux Finding Score with Voice Disability Severity in Patients with Laryngopharyngeal Reflux - I Gusti Ayu Karindra Dewi; Putu Dian Ariyanti Putri (International Journal of Psychology and Health Science, 2026)
Laryngopharyngeal reflux (LPR) is a frequent cause of dysphonia, yet how reflux severity relates to voice disability is not fully characterized. Most prior studies used only the self-reported Voice Handicap Index, leaving perceptual and objective voice measures under-examined. This study assessed the correlation of the Reflux Symptom Index (RSI) and Reflux Finding Score (RFS) with voice disability, evaluated simultaneously by the subjective GRBAS scale and VHI-10 and the objective maximum phonation time (MPT), in patients with LPR. A cross-sectional analytic study enrolled 26 patients with LPR-related dysphonia at a tertiary ORL-HNS clinic between February and April 2026. LPR was defined by RSI >13 and/or RFS >7. Because the score data were non-normally distributed, associations were analyzed with Spearman rank correlation. Median RSI was 17.00 and median RFS 7.50. Most patients had moderate voice disability. RSI and RFS correlated positively with grade, roughness, breathiness, and VHI-10, and negatively with MPT (RSI–MPT ρ=−0.713, RSI–VHI-10 ρ=0.896, RFS–MPT ρ=−0.813, RFS–VHI-10 ρ=0.781, all p<0.001). Combining RSI and RFS with multidimensional voice assessment identifies LPR patients at risk of voice impairment and reduced phonatory efficiency.